Impact of healthcare system collapse on hospital-acquired infection dynamics: a mathematical approach - Shaale, Maria M.; Joel, Luke O.; Nyabadza, Farai (Frontiers in Applied Mathematics and Statistics, 2026)
The collapse of healthcare systems poses a serious threat to hospital environments, increasing the spread of nosocomial infections. Limited resources, overcrowding, and weakened infection control measures allow harmful pathogens to persist on surfaces, medical equipment, and in the air. Consequently, patients and healthcare workers face a higher risk of infection, leading to increased morbidity. In this study, we develop a mathematical model to examine how a failing healthcare system influences the spread of nosocomial infections in hospitals. The model properties, such as the positivity and boundedness of solutions, are established. The disease-free equilibrium is determined and its stability is analyzed using the basic reproductive number R0. Model simulations are performed to determine the influence of some important parameters on the reproduction number of the model. The findings show that a collapsing healthcare system significantly affects the control of nosocomial infections in hospitals, as inadequate infection control measures lead to a more contaminated environment. Therefore, strengthening healthcare systems is essential to reducing nosocomial infections and ensuring safer hospital environments. These results have huge implications for the management of nosocomial infections in hospitals.2000 MSC: 34C11, 34C60, 92B05